2003
DOI: 10.1097/00042737-200302000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Association of coeliac disease with primary biliary cirrhosis in Poland

Abstract: Our results from Poland do not confirm a high prevalence of coeliac disease in PBC patients. Guinea-pig liver transglutaminase immunolinked assay cannot be used as a screening test for coeliac disease in PBC patients. A gluten-free diet may be helpful in restoration of liver function in patients with such an association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…A threefold or greater increase in risk of PBC in people with CD compared with the general population has been recently demonstrated [66,67]. There are, however, some reports that do not confirm the association between CD and PBC [68,69]. Given the small number of patients studied in these reports, the association between CD and PBC can be reasonably accepted.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 94%
“…A threefold or greater increase in risk of PBC in people with CD compared with the general population has been recently demonstrated [66,67]. There are, however, some reports that do not confirm the association between CD and PBC [68,69]. Given the small number of patients studied in these reports, the association between CD and PBC can be reasonably accepted.…”
Section: Primary Biliary Cirrhosismentioning
confidence: 94%
“…With the exception of two negative studies, consistent association between PBC and CD has been shown. [36,37] In a recent review of CD and liver disease, percentage of biopsy confirmed CD cases among the PBC population ranged from 1.3 to 7%. [38] The largest study included greater than 13,800 CD patients from the Swedish national register and confirmed the association.…”
Section: Associated Autoimmune Liver Diseasementioning
confidence: 99%
“…The association of coeliac disease (CD) with various forms of liver disease has been described in several European and North American populations 1–14 . In particular, an increased prevalence of the autoimmune cholestatic liver diseases; primary biliary cirrhosis (PBC) and primary sclerosing cholangitis (PSC), in patients with CD has been reported.…”
Section: Introductionmentioning
confidence: 99%